RELIGIOUS/SPIRITUAL COPING: A STUDY WITH FAMILY CAREGIVERS OF CHILDREN AND ADOLESCENTS UNDERGOING CHEMOTHERAPY - Rosangela Garcia Jaramillo; Pedro Sadi Monteiro; Moema da Silva Borges (Universidade Federal do Paraná, 2019)
Objective: To identify the style of religious-spiritual coping used by family caregivers of children and adolescents undergoing chemotherapy.Method: Quantitative descriptive study. Data from 63 family caregivers in a pediatric hospital in Distrito Federal was collected through a questionnaire for characterization of the sample and the religious/spiritual coping scale. Statistical Package for the Social Sciences version 16.0 and Microsoft Excel 2013 were used in the analysis.Results: The total value of religious/spiritual coping obtained was 3.7. The mean value of positive religious/spiritual coping was 3.4 and of negative religious/spiritual coping was 2. The negative religious/spiritual coping (NRSC)/positive religious/spiritual coping (PRSC) ratio was 0.6, with a tendency for the use of negative strategies in religious/spiritual coping.Conclusion: Family caregivers used religious-spiritual coping through positive and negative strategies, with a predominance of negative strategies. These results support nursing care by associating the competencies for care delivery in the physical dimension to the spiritual needs of the family unit.